Zimbabwe Institute of Development Studies (ZIDS): The Early Context of Sam Moyo’s Intellectual Development - Raftopoulos, Brian (Agrarian south : journal of political economy, 2016)
One of the key sites of Sam Moyo’s early intellectual development was the Zimbabwe Institute of Development Studies (ZIDS). Established by the newly independent Zimbabwean government in the early 1980s to provide an alternative intellectual space for considering socialist policy alternatives, the Institute was subject both to the opportunities and to challenges of state politics. In his work at ZIDS, Sam drew on a long history of radical political economy studies on Zimbabwe, as well radical Africanist thought to pursue his seminal work in agrarian studies. In the midst of a highly contested fast-track land reform programme, Sam led the way in understanding not only the economic challenges of the programme but also the opportunities that it opened up to move beyond the unequal legacies of the settler-colonial agrarian political economy. However, while Sam pioneered the study of the changing forms of agrarian production relations in the 2000s, he focused less on the changing forms of political rule in the country. Into this space, a rich literature from different disciplinary frameworks has emerged and expanded the debate on agrarian and political change in Zimbabwe.